Muscle activity detection of human upper limb using piezoelectric based sensory system - Rozi, M. Hanif Farhan; Nordin, Nor Hidayati Diyana; Jasni, Farahiyah (Persatuan Saintis Muslim Malaysia (PERINTIS), 2023)
Electromyography (EMG) has widely been used for muscle activity detection and is proven accurate. However, using EMG requires lots of preparation and it is time consuming. Thus, this motivates the exploration of alternative methods. Materials with piezoelectricity effect have gained its popularity not only in the area of structural vibration but have alse emerged as viable sensing elements for capturing biosignals due to its lightweight and flexibility. This research investigates the effectiveness of polyvinylidene fluoride (PVDF) film length in capturing biceps brachii muscle activity during arm flexion and extension. Two films of different lengths were attached to a healthy male subject’s arm at specific flexion angles (0°, 90° and 145°) for 30 seconds. The experiment was also repeated with a load of 4 kg and 7kg. It is seen that shorter PVDF film exhibits better performance with an increase of 29.16% peak-to peak voltage at maximum activation . In addition, the higher the load, the higher the voltage generated by the PVDF film. Hence, this study suggests that shorter PVDF is more suitable for muscle activity detection.